PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DAN STUDENT TEAMS ACHIEVEMENT DIVISION - Maryani, Maryani; Fachruddin S., M.; Maizora, Syafdi (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2017)
AbstractThe purpose of this research is to find out the difference between the result of student learning which taught by cooperative learning Group Investigation type and Student Teams Achievement Division type on polyhedron in the class VIII of Junior High School 4 Bengkulu City. This research is quasy experiment research with population in this research is the student in class VIII of Junior High School 4 Bengkulu City. The sample in this research is get from cluster sampling, so the experiment class (VIII4) are 35 students by using Group Investigation an control class (VIII5) are 34 students by using Student Teams Achievement Division. Based on data analysis by using t test is get tcount=0,02 and ttabel with ? = 0,05, df = 66 get ttabel = 2,00, so tcount is placed between -2,00 ? tcount ? 2,00. This matter, H0 accepted which means there is no significant differences between the result of student learning between cooperative learning Group Investigation type and Student Teams Achievement Division type in class VIII of Junior High School 4 Bengkulu City.Keyword:result of student learning, GI, and STAD